Kebijakan Penanggulangan Kejahatan Studi Terhadap Resolusi Kongres PBB VIII/1990 Tentang Computer-Related Crime - Bahiej, Ahmad; Ach. Tahir, Ach. Tahir (UIN Sunan Kalijaga, 2012)
The research aims at exploring and finding the fact on implementation of resolution of the Nation Union Congress VIII/1990 on Computer-related Crime at State Islamic University of Sunan Kalijaga. It is significant to know what extent the university responds to national and international issues on development of cyber crime. The university, the oldest institution of islamic studies in Indonesia, has moralistic responsibility for encouraging the government in implanting awareness on development and danger of cyber crime for people, in particular for the university’s lectureres, students, and administrative officers. It is a field research strengthened by library data and based on normatively -empirically-qualitatively legal approach. Its objects are curriculum, regul ations, deans or vice deans of academic affairs, Centre for Computer and Information System of State Islamic University of Sunan Kalijaga, and libraries around the university. The data are collected through depth interwiew with the rector or vice rectors, deans or vice deans, director of the centre, chairman of libraries, and several communities of hackers. In addition, the data collection is strengthened by spreading questionnaires to the university’s students in deal with students’ behaviors on internet.